A narrative study of teachers' life stories and their work identity - Heaton, Pamela Jane (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
Media coverage of the poor state of this country's education system has described public images of the teaching profession which provide a context for the research described in this paper. The research is concerned with how and to what extent work identity is reflected in the life stories of five female teachers from a rural village in the Eastern Cape. A social constructionist approach is taken to the meaning and construction of identity, and the paper describes the process of a narrative method of analyzing and interpreting the stories. An initial analysis reveals that the participants had few career options and little choice of career. Further analysis is concerned with interpreting how the teachers create coherence in their stories around this lack of choice as well as within the larger social and historical context. Simultaneously there is an interpretation of the participants' work identity. The teachers create coherence in their narratives around their families and their socioeconomic or cultural circumstances, but make no explicit reference to the political context of their work choices, which were made in the context of the restraints of the Apartheid era. From each teacher's story an understanding of their unique work identity emerges. These alternative understandings provide a contrast to the images constructed by the media.
Keywords: Identity (Psychology) -- Case studies; Teachers -- Case studies; Women teachers -- South Africa; Education -- South Africa -- History; Education -- South Africa -- Eastern Cape; Women teachers -- South Africa -- Eastern Cape